Recommendations for ototoxicity surveillance for childhood, adolescent, and young adult cancer survivors: a report from the International Late Effects of Childhood Cancer Guideline Harmonization Group in collaboration with the PanCare Consortium. Issue 1 (January 2019) - Clemens, Eva; van den Heuvel-Eibrink, Marry M; Mulder, Renée L; Kremer, Leontien C M; Hudson, Melissa M; Skinner, Roderick; Constine, Louis S; Bass, Johnnie K; Kuehni, Claudia E; Langer, Thorsten; van Dalen, Elvira C; Bardi, Edith; et al.
Summary: Childhood, adolescent, and young adult (CAYA) cancer survivors treated with platinum-based drugs, head or brain radiotherapy, or both have an increased risk of ototoxicity (hearing loss, tinnitus, or both). To ensure optimal care and reduce consequent problems—such as speech and language, social–emotional development, and learning difficulties—for these CAYA cancer survivors, clinical practice guidelines for monitoring ototoxicity are essential. The implementation of surveillance across clinical settings is hindered by differences in definitions of hearing loss, recommendations for surveillance modalities, and remediation. To address these deficiencies, the International Guideline Harmonization Group organised an international multidisciplinary panel, including 32 experts from ten countries, to evaluate the quality of evidence for ototoxicity following platinum-based chemotherapy and head or brain radiotherapy, and formulate and harmonise ototoxicity surveillance recommendations for CAYA cancer survivors.